Communication difficulties in Children Aged 3-13 Years with Down Syndrome attending Kampala School for Physically Handicapped in Kampala district. - Kakooza, Alex (Student's Journal of Health Research Africa, 2021)
Background: Communication difficulties among children with Down syndrome are not only a problem in Uganda, but it’s a worldwide problem. Such difficulties affect the child’s ability to comprehend, detect or apply language and speech to engage in discourse effectively with others. Therefore this study was done to assess the communication difficulties in children aged 3-13 Years with Down Syndrome Attending Kampala School for Physically Handicapped in Kampala District Methodology: The study was a descriptive cross-sectional study where quantitative and qualitative methods were employed in data collection. The study involved 25 respondents who consisted of male and female children aged 3-13 years who were selected by a non-probability Sampling design Results: A total of 25 children aged 3-13 years with Down syndrome were assessed in June 2016. 18 (72 %) children had communication difficulties and 7(28%) did not have any communication difficulties. 56 were males and 44 were females. The common communication difficulties in school-going children aged 3-13 with Down syndrome at Kampala School for Physically Handicapped included intelligible speech (25, 100%) and inability to perceive objects and communicate with others in their environment 14 (56 %) among others. Conclusion and recommendations: The prevalence of communication difficulties was high and such difficulties impended children to communicate hence affecting their learning process. It was recommended that the government through the Ministry of Education should equip schools with more skilled manpower especially special needs teachers, speech and language therapists, and other multidisciplinary school team professionals, and school administration should design speech and language treatment programs for each child based on his/her communication pattern and needs.